2008
DOI: 10.3892/or.19.6.1405
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the thyroid-stimulating hormone receptor in poorly-differentiated carcinoma of the thyroid

Abstract: Abstract. Poorly-differentiated carcinomas (PDCs) occupy an intermediate position between differentiated (follicular and papillary) and undifferentiated carcinomas (UDCs) based on morphology and behavior. However, its definition remains unclear, especially in the differentiation of thyroid function. To characterize the hormonal differentiation of PDCs, in addition to the morphological definition, we immunohistochemically investigated the thyroid-stimulating hormone receptor (TSHR) and thyroid transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Some studies have implied that TSH could act to initiate thyroid carcinogenesis [36,37], and suggested that high TSH concentrations are closely associated with an increased risk of thyroid cancer [32][33][34][35]. However, other reports have disputed this possibility [38][39][40]. Previously, we crossed the Thrb PV/PV mouse, a model of follicular thyroid cancer, with mice deficient in the TSH receptor gene (TSHR À/À mice).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have implied that TSH could act to initiate thyroid carcinogenesis [36,37], and suggested that high TSH concentrations are closely associated with an increased risk of thyroid cancer [32][33][34][35]. However, other reports have disputed this possibility [38][39][40]. Previously, we crossed the Thrb PV/PV mouse, a model of follicular thyroid cancer, with mice deficient in the TSH receptor gene (TSHR À/À mice).…”
Section: Discussionmentioning
confidence: 99%